Теоретичні аспекти трансформації інституту корупційних злочинів - Михайленко Дмитро Григорович; Mychailenko D.G. (Одеса : Юридична література, 2014)
The article focuses on certain problems of the Criminal Code of Ukraine under the conditions of enhancement of the legal mechanism of fight against corruption crimes. The imperfection of the Criminal Code is shown in regard to establishing the grounds of criminal liability of legal entities. The structure of a target of corruption crimes is described as a group of guarded legal relations. A hypothesis about the establishment of a model of criminal law fight against corruption based on the principle of “multiple borderlines” is set up. The urgency and necessity of constructing a new scientific theory of corruption crimes is substantiated. В статье исследуются некоторые проблемы УК Украины в условиях проведения модернизации правового механизма противодействия коррупционным преступлениям. Показывается несовершенство УК в части установления оснований уголовной ответственности юридических лиц. Описывается структура объекта коррупционных преступлений, как группы охраняемых правоотношений. Выдвигается гипотеза о построении модели уголовно-правового противодействия коррупции по принципу «многорубежности» и обосновывается актуальность и необходимость конструирования новой научной теории – теории коррупционных преступлений.
The issues of enhancement of the legal mechanism of corruption crimes counteraction in Ukraine
Михайленко Д.Г. Теоретичні аспекти трансформації інституту корупційних злочинів / Д.Г.Михайленко // Актуальні проблеми держави і права : збірник наукових праць. Вип. 74 / редкол.: С. В. Ківалов (голов. ред.) та ін. ; відп. за вип. В. М. Дрьомін. – Одеса : Юридична література, 2014. – С.338-346.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; коррупция; коррупционные преступления; уголовная ответственность юридических лиц; лица, которые предоставляют публичные услуги; теория коррупционных преступлений; corruption; corruption crimes; criminal liability of legal entities; public service providers; the theory of corruption crimes; корупція